DESIGNING OF LOCATION MONITORING APPLICATION IN THE TANGERANG REGION WHICH IS SHOCKING WATER SOURCES BASED ON ANDROID - Suci Lestari Nasution, Winda; Nusa, Patriot (Journal of Computer Science and Technology (JCS-TECH), 2023)
Android is an operating system that is specifically designed for smartphones and tablets. This Android system has a Linux base which is used as the basic foundation of the Android operating system. Linux itself is an operating system that is specifically designed for computers. Resources in the form of water that are useful or potential for humans, difficulties in monitoring water sources are an obstacle that is currently felt by the community. With the help of current technological advances, namely IoT (Internet of Things) can reduce the problem that exists today, using only an android smartphone. Android smartphones function to send and receive information via the internet network and also make communication easier. This application can monitor community water sources by obtaining notifications that are in water sources. With this, people can enjoy a healthier life because they can control the cleanliness of water sources easily and practically.